Obesity Trends among Asthma Patients in the United States: A Population-based Study. Issue 1 (22nd January 2019) - Lurbet, Maria Fernanda; Rojano, Belen; Whittaker Brown, Stacey-Ann; Busse, Paula; Holguin, Fernando; Federman, Alex D.; Wisnivesky, Juan P.
Background: Obesity is strongly associated with worse asthma control and poorer quality of life. The current obesity epidemic has reached historically high levels, with an estimated prevalence rate of 37% in the general United States (US) population. However, less is known about trends in the prevalence of obesity among individuals with asthma or which sociodemographic groups are at higher risk for increased weight. Methods: The study was conducted with data from the Behavioral Risk Factor Surveillance System (BRFSS) study, a nationally representative probability-based sample of the US population. We included participants ≥18 years of age who were interviewed between 1999 and 2016. Using stratified weighting, we estimated the annual prevalence of participants with, and without a diagnosis of asthma, classified according to their body mass index (BMI), into: normal weight (18.5–25 kg/m 2 ), overweight (25–30 kg/m 2 ), or obese (>30 kg/m 2 ). We calculated the annual odds of obesity among participants with vs. without asthma to assess if trends among individuals with asthma followed those of the general US population. Nominal regression analysis assessed the association between age, sex, race/ethnicity, and income with prevalence of obesity among participants with asthma. Results: Among the 543, 574 BRSFF participants with asthma, the prevalence of overweight and obesity changed from 34.3% and 24.7% in 1999 to 28.8% and 41.1% in 2016, respectively. The odds ratio (OR) of obesity in patients with asthma compared to the general population without asthma, increased during the same period from 1.39 (95% confidence interval [CI]: 1.36–1.36) in 1999 to 1.75 (95% CI: 1.75–1.76) in 2016. Adjusted analysis showed that older (OR: 2.32, 95% CI: 2.32–2.33), Black (OR: 1.61, 95% CI: 1.61–1.61) and Hispanic (OR: 1.29, 95%. CI: 1.28–1.29) participants with asthma had higher rates of obesity. Conclusions: There has been a substantial increase in the prevalence of obesity among individuals with asthma in the last two decades, beyond what could be explained by general population trends. These results suggest that obesity is an increasing determinant of asthma morbidity and should be particularly targeted in minorities with asthma.